THE EFFECT OF APPLYING VITAMIN D ONREPAIRING OF THORAX PHOTO OF TUBERCULOSIS PATIENTS OF BATAK ETHNIC IN MEDAN - Seri Rayani Bangun; Bintang Y.K. Sinaga; Nasipta Ginting (Science Midwifery, 2021)
This study aims to determine the effect of vitamin D on the repairingof thoracic on patients with pulmonary tuberculosis of Batak ethnic in Medan, conducted on 42 patients with TB, vitamin D group of 21 people and 21 placebo. Giving vitamin D dose of 2.5 mg (100,000 IU) for 4 times (weeks 0, 2, 4, 6) and placebo for 4 times (weeks 0, 2, 4, 6). B. The assessment of vitamin D and thorax photo were done before and after intervention.The results showed that the levels of vitamin D results before and after there is a difference, the measurement results using the enzyme linked immunosorbent assay (ELISA) provisions of the absorbance of each well at a wavelength of 450 ± 10 nm.Vitamin D levels were measured 25 (OH) D nmol / L then further analyzed using paired T test on vitamin D group p = 0:00, mean difference 29.27 + vitamin D levels were 22 ng / ml, whereas the placebo group p = 0:27, the difference of the mean levels of vitamin D 1:36 + 5:53 ng / ml. After examination of thorax photo in hospital then analyzed using Chi-square test. Vitamin D group showed a total improvement (66.7%) while the placebo treatment (33.3%), p = 0:06 concluded there was no effect of vitamin D on the restoration of thorax photo on patients pulmonary tuberculosis Batak ethnic.